TikTok Sebagai Media Pembelajaran Maharah Al-Kalam di Jurusan Pendidikan Agama Islam STAI Ma’had Aly Al-Hikam Malang - Rokhman, Imam Athoir (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeru Sultan Aji Muhammad Idris Samarinda, 2024)
The discussion on the use of TikTok in Arabic language learning shows that TikTok has potential as an interactive learning medium. However, more attention is needed in its use in the context of Arabic language learning. Therefore, this study aims to fill the gap by describing the utilization of TikTok in Arabic language learning, especially in speaking skill in the Islamic Religious Education Department at STAI Ma'had Aly Al-Hikam Malang. This research uses a descriptive qualitative approach, with observation and interviews as data collection techniques. The results of this study indicate that the use of TikTok as a learning media for speaking skill can improve the quality of students' learning experience because the content is interesting and interactive. The learning process involves preparation, implementation and evaluation stages, where the instructor is responsible for selecting materials, uploading them to the TikTok account, and using the platform to deliver lessons through videos. Positive reinforcement and stimulation are also important to support student learning.